Ernst Troeltsch : Leben und Werk - Drescher, Hans-Georg 1929-2008 (Vandenhoeck & Ruprecht, 1991)
Hans-Georg Drescher: "Ernst Troeltsch". Leben und Werk. Vandenhoeck & Ruprecht, Göttingen 1991. 558 S., 12 Abb., 98,- DM